2014
DOI: 10.1159/000366022
|View full text |Cite
|
Sign up to set email alerts
|

HuD Promotes Progression of Oral Squamous Cell Carcinoma

Abstract: Head and neck cancer, including oral squamous cell carcinoma (OSCC), ranks as the sixth most common malignancy worldwide. Overall 5-year survival rates of OSCC have not significantly improved during the past 3 decades and the 5-year survival rate is less than 50%. Several invasion grading systems have been employed in OSCC, however, their utility is still controversial. HuD belongs to the Hu protein family and acts as an RNA-binding protein involved in mRNA stability and translational regulation. Although HuD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…This confounding result motivated us to check the potential role of these proteins in cancers. Though ELAVL1 (HuR) is a well-studied protein, limited reports exist for roles of the other three family members in cancers [45–48]. The downregulated members are established to have neuronal restricted expression and some of them have been reported to have a putative tumor suppressor role.…”
Section: Discussionmentioning
confidence: 99%
“…This confounding result motivated us to check the potential role of these proteins in cancers. Though ELAVL1 (HuR) is a well-studied protein, limited reports exist for roles of the other three family members in cancers [45–48]. The downregulated members are established to have neuronal restricted expression and some of them have been reported to have a putative tumor suppressor role.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, HuD is a useful diagnostic and therapeutic target in OSCC. As MMP-2 and -9 are components of the epithelial basement membrane and extracellular matrix proteins, HuD could be a novel modulator for the tumor microenvironmental modification in OSCC [114]. Furthermore, our results suggested that HuD is newly detected target of VEGF-A–mediated angiogenesis in OSCC.…”
Section: Novel Prognosticators Of Osccmentioning
confidence: 75%
“…Previously, HuD expression has been reported in small cell lung carcinoma and neuroblastoma [112,113]. In addition, we previously reported that HuD regulated the invasion ability and activation of caspase-3, and the main target genes in OSCC cells of HuD are VEGF-A , VEGF-D , MMP-2 , and MMP-9 [114]. In OSCC specimens, HuD expression was detected in 36.6% (30/82), and its expression closely correlated with the histological differentiation of the tumor, nodal metastasis, and diffuse invasion pattern.…”
Section: Novel Prognosticators Of Osccmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is the most common epithelial malignancy in oral cavity, with 354 864 new cases diagnosed worldwide and 177 384 deaths every year . Despite advances in cancer management, the overall 5‐year survival rate of OSCC patients has remained less than 50% and has not improved significantly during the past three decades . Major reason for this circumstance is the tendency of OSCC to invade adjacent tissues and metastasis, with the local and regional recurrence rate ranging from about 33% to 40% .…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite advances in cancer management, the overall 5-year survival rate of OSCC patients has remained less than 50% and has not improved significantly during the past three decades. 2 Major reason for this circumstance is the tendency of OSCC to invade adjacent tissues and metastasis, with the local and regional recurrence rate ranging from about 33% to 40%. 3 More detailed studies are required to understand the mechanisms mediating invasion and metastasis of OSCC in order to prolong patients' survival.…”
Section: Introductionmentioning
confidence: 99%